ORAL HYGIENE HABITS AND ORAL HEALTH STATUS OF FEMALE ADOLESCENTS UNDER STATE PROTECTION: A PILOT STUDY - Cenker Zeki Koyuncuoğlu; Mağrur Kazak; Ferda Pamuk; Emine Çifcibaşı (Istanbul University, 2017)
Purpose: The aim of this study is to evaluate oral health status and oral hygiene practices of female adolescents under state protection. Subjects and Methods: Fifty-five female participants between the age of 12 and 18 who are under the care of The Child Protection Institution were included in this study. Self-administered questionnaires were used to obtain information regarding knowledge of oral health and habits. Dental caries status was scored according to the criteria of the World Health Organization (WHO), using the indices of Decayed (D), Missing (M), Filled (F), Surfaces (S) (DMFS). In addition, Gingival Index (GI) and Plaque Index (PI) were recorded during periodontal assessment. Data were statistically analyzed by using Oneway analysis of variance, Tukey's HSD and Student's t tests. Results: Fourteen children had dental fear and 52.7% of them were not satisfied with their esthetic appearance. Although 78.2% of the children knew that brushing prevents dental caries, only 18 of them were brushing regularly twice per day. Mean DMFS, GI and PI scores were 13.18±5.68, 1.35±0.37 and 1.33±0.45, respectively. Only 20% of the children were using dental floss. There was statistically no significant difference between the DMFS scores of the children in terms of flossing. However, the difference between the mean GI and PI of the same group was found to be statistically significant (p<0.05). Conclusion: Children under state protection were found to have a reasonable knowledge of the causes of dental caries and gingival bleeding. Therefore, adequate management of this positive attitude can significantly improve the oral health of this population.